IBN RUSYD DAN METODE IJTIHÂD-NYA DALAM KITAB BIDÂYAT AL-MUJTAHID - Fahruddin Ali Sabri Fahruddin Ali Sabri (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2010)
Abstract: Ushûl  fiqh has a significant role in Islamic science, since Islamic lawpartly regulates the essential problems not the detail ones. It became nature because Islamic law rules by the end of time. However in human being live there must always be change of social design, so that it always araises new problem in society. This article is to describe the Ibnu Rusyd’s method in deciding syar’i law. His capacity as fiqih expert is undoubtful. His masterpiece, Bidâyat al-Mujtahid wa Nihâyat al-Muqtashid is a comparison of fiqh book Key Words: Ibn Rusyd, ijtihâd, dan hukum Islâm